Deceit and Disappointment In Born On the Fourth of July By Ron Kovic (International Journal of Scientific Research and Management (IJSRM), 2025)
This article aims at exploring the themes of deceit and disappointment in Ron Kovic’s autobiographical novel entitled Born on the Fourth of July which deals with the horrible consequences of the Vietnam war in America, and more particularly in the lives of Vietnam veterans both physically and psychologically. The novel gives an account of Ron Kovic’s journey from an enthusiastic Marine, to a disillusioned veteran, putting the emphasis on how society and his illusion led to his disappointment. Born on the Fourth of July is an outstanding autobiographical novel, a best-seller that was turned into a 1989 film starring Tom Cruise and directed by Oliver Stone. In this novel, Kovic describes his transformation from a gung-ho soldier into an ardent dissenter. However, through a psychological analysis, we will delve deep into the impact of the Vietnam War on the American society in general, and in particular on Kovic’s identity and mental health after having been betrayed by the country for which he fought with commitment and pride.